DIFFERENTIAL PULSE ANODIC STRIPPING VOLTAMMETRY FOR DETERMINATION OF SOME HEAVY METALS IN URANIUM - Saryati Saryati (Indonesian Journal of Chemistry, 2009)
The direct determination of some metals impurity in uranium by using differential pulse anodic stripping voltammetry (DPASV) method at a hanging mercury drop electrode and in a carbonate buffer media was developed. It was found that the carbonate buffer show the strongest affinity for uranium and gives the best separation between the DPASV peaks of heavy metals impurities. The carbonate concentration markedly affects the oxidation and reduction the major and the minor constituents of the uranium samples. In 0.1 M carbonate buffer solution pH 10, copper, bismuth, thalium, lead, cadmium, zinc, could be determined without the removal of the uranium matrix. Recovery and relative standard deviation (RSD) of this method was in the range of 174% - 85.2% for recovery and 36.8% - 1.2% for RSD. The larger error of analytical result was obtained for Zn at low concentration. In general, the analytic results error and RSD decreased with increasing metals concentration.